Research methodology in geopolitics: application of qualitative content analysis in studying the geopolitical codes case: the role of the Persian Gulf's oil in the Iraq war - Naji, Saeid; Jawan, Jayum; Redzuan, Ma'rof (Addleton Academic Publishers, 2011)
This paper attempts to analyze geopolitical codes using qualitative content analysis. Analyzing such codes helps to reveal the political elite's geopolitical assumptions, which form a state's foreign policy. This paper explains how the relationship between events and geopolitical codes could be interpreted by using qualitative content analysis method. It shows that this technique is researcher centric and how effective it is depends on the ability and skill of the researcher. A qualitative content analysis is also important because, for analyzing geopolitical codes, the researcher needs to analyze and interpret presidential speeches and governmental documents as critical data. In this paper a case study is used to explain the process of analysis, including different stages of this technique.